2022
DOI: 10.13057/biodiv/d230157
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral, physiological, and blood biochemistry of Friesian Holstein dairy cattle at different altitudes in West Java, Indonesia

Abstract: Abstract. Tanuwiria UH, Susilawati I, Tasrifin DS, Salman LB, Mushawwir A. 2021. Behavioral, physiological, and blood biochemistry of Friesian Holstein dairy cattle at different altitudes in West Java, Indonesia. Biodiversitas 23: 533-539. For dairy cows, the study of physiological aspects and those related to it is very important based on altitude. The data of this study are the main considerations to determine the ability of homeostasis, prediction of production and appropriate feed management. This study ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…The polar and bipolar nature of chitosan (binds water and fat) will increase the viscosity of digesta, so that the feed digesta rate is faster and will reduce nutrient contact with the small intestine during absorption, thereby reducing villi development [24][25][26][27]. Another factor is that early administration of chitosan inhibits the expression of genes or proteins that regulate lipid metabolism [27][28][29][30]. As a result, villi growth and development are reduced, as well as suppressing the activity of the ileum in carrying out its function as the absorption intestine.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The polar and bipolar nature of chitosan (binds water and fat) will increase the viscosity of digesta, so that the feed digesta rate is faster and will reduce nutrient contact with the small intestine during absorption, thereby reducing villi development [24][25][26][27]. Another factor is that early administration of chitosan inhibits the expression of genes or proteins that regulate lipid metabolism [27][28][29][30]. As a result, villi growth and development are reduced, as well as suppressing the activity of the ileum in carrying out its function as the absorption intestine.…”
Section: Resultsmentioning
confidence: 99%
“…Glutathione induction in this study means adding concentrations of amino acids, especially glutamine, cysteine and glycine. The three amino acids are related to growth, as reported by [18] that amino acids, especially glutamine, play an important role for growth-related nutrient pathways and regulation of cell proliferation, preventing apoptosis [27], and even stimulating the synthesis of specific proteins related to tissue growth [28].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the role of DP administered through feed, several researchers have previously reported that the administration of DP in feed is able to improve the rhythm and rate of metabolism in livestock, and show good physiological responses [17,18,[25][26][27][28][29]. Other researchers have shown that feeding probiotics to animals and livestock has an impact on their biochemical profiles.…”
Section: Resultsmentioning
confidence: 99%
“…According to [36,37] SGOT levels in laying hens increased SGOT levels can be caused by fatigue in certain organs, causing free radicals. Fatigue, inflammatory conditions of lipid peroxidation, infection can cause increased free radicals.…”
Section: Resultsmentioning
confidence: 99%